Virtual Reality Project Car Manufact Simulator grabs visitors attention - Naqiah, Puaad (UMPSA, 2024)
GAMBANG, 2 June 2024 - The Virtual Reality Project ‘Car Manufact Simulator’ by Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) student, Amirul Aidil Hasnul Azan grabbed the attention of visitors at the Advanced@TVET UMPSA booth during the recent Jom Masuk U 2024 East Zone II at the Sports Complex Hall, UMPSA Gambang Campus.